Call for Papers: The Game, a Gamified Tool for Teaching Scientific Writing in Engineering Students - Núñez-Pacheco , Rosa; Vidal Duarte, Elizabeth; Turpo-Gebera, Osbaldo; Castro-Gutiérrez, Eveling (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This paper presents the evaluation of the alpha version of a gamified tool called Call for Papers: The Game (CfP:TG), specially designed for teaching scientific writing in the training of future engineers. A non-probabilistic convenience sampling was carried out with the participation of engineering students from a Peruvian public university. The short version of the user experience questionnaire (UEQ) was applied, and usability was qualitatively evaluated. The main results indicate that the Pragmatic Quality of CfP:TG is in the neutral range with a value of 0.729, and the Hedonic Quality receives a positive evaluation with a value of 1.089.